1998
DOI: 10.1097/00005072-199805000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gene Expression in Human Astrocytoma Cells Selected for Migration

Abstract: Human glioma cells from a long-term cell line were selected for their ability to migrate on a glioma-derived extracellular matrix. When tested over 28 serial passages, the migration-selected strain showed a genetically stable, enhanced migration rate compared with the parental cells. Proliferation studies demonstrated that the growth rate of migration-selected cells was slightly arrested. Both the selected strain and the parental culture showed anchorage-independent growth in soft agarose and were tumorigenic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 0 publications
1
40
0
1
Order By: Relevance
“…TXSA, an enzyme operating downstream of the COX, has recently been identified as an antiapoptotic and invasion-associated factor in several human cancers (McDonough et al, 1998;Daniel et al, 1999;Giese et al, 1999;Rodrigues et al, 2001;Kurzel et al, 2002;Yoshizato et al, 2002). In this study, we demonstrate for the first time that p53 and ets-1 regulate transcription of the TXSA gene in an antagonistic manner.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…TXSA, an enzyme operating downstream of the COX, has recently been identified as an antiapoptotic and invasion-associated factor in several human cancers (McDonough et al, 1998;Daniel et al, 1999;Giese et al, 1999;Rodrigues et al, 2001;Kurzel et al, 2002;Yoshizato et al, 2002). In this study, we demonstrate for the first time that p53 and ets-1 regulate transcription of the TXSA gene in an antagonistic manner.…”
Section: Discussionsupporting
confidence: 56%
“…Furthermore, experimental overexpression of TXSA promotes tumor growth in vivo, which has been demonstrated in an adenocarcinoma mouse model (Pradono et al, 2002). Although the cancerpromoting effects of TXSA remain poorly understood, it appears that high levels of TXSA enhance angiogenesis and increase the invasive potential of neoplastic cells (McDonough et al, 1998;Giese et al, 1999;Rodrigues et al, 2001;Kurzel et al, 2002;Yoshizato et al, 2002). TXSA may also play a certain role in rendering tumor cells resistant to apoptosis, and we have recently reported that specific inhibitors of TXSA block motility and sensitize migration-arrested glioma cells to apoptosis (Yoshizato et al, 2002).…”
Section: Introductionmentioning
confidence: 97%
“…Now an important role of TXSA as a tumor promoting factor emerges. Experimental overexpression of TXSA promotes tumor growth in vivo [4], and it appears that high levels of TXSA enhance angiogenesis and increase the invasive potential of neoplastic cells [2,3,[5][6][7]. In human gliomas TXSA renders tumor cells resistant to apoptosis and we have demonstrated that specific inhibitors of TXSA block motility and sensitize migration arrested glioma cells to apoptotic cell death [7].…”
Section: Introductionmentioning
confidence: 94%
“…We have previously shown that furegrelate, a pharmacological inhibitor of TXSA which impedes the metabolic conversion of cyclic endoperoxide into TXA-2, induces apoptosis in glioma cell lines in vitro [2,3,[5][6][7]. In this study, we examined the effects of furegrelate on the radio response in glioma cells.…”
Section: Introductionmentioning
confidence: 99%
“…In prostate cancer, the expression of thromboxane synthase was increased in tumor specimens of advanced stage and grade and particularly in the areas of perineural invasion (15,16). Thromboxane synthase expressed in prostate cancer cells was enzymatically active and may play a contributory role in tumor progression, especially tumor cell motility (15,17,18).…”
Section: Introductionmentioning
confidence: 99%